Feeding the hungry heart : the experience of compulsive eating - Roth, Geneen (New York, U.S.A. : Signet Book, 1983)
That is how Geneen Roth remembers her year as a compulsive overeater and self-starver. But she broke free from the destructivecycle of compulsive eating, and went on to help other women do the same.
Contents Introduction 1 Is there life after chocolate 6 BINGEING: YOU CAN NEVER EAT ENOUGH OF WHAT YO DON'T REALLY WANT 13 BODY IMAGE BEING AND/OR FEELING FAT 33 EATING AS METAPHOR PART 1: HUNGER 93 EATING AS METAPHOR, PART 2: NOURISHMENT 137
Incluye Contents
Keywords: ENGLISH LITERATURE; COMPULSIVE EATING